The relationship between frailty incidence and polypharmacy in the elderly age group in Melinggih Village, Gianyar Regency, Bali - Pemayun, Tjokorda Istri Ratih Pradnyandari; Aryana, I Gusti Putu Suka (Published by Universitas Gadjah Mada, 2025)
The risk of the elderly population experiencing frailty is more significant in women than man. Several factors are associated with the frailty include the pattern of women’s daily activities being more than men’s, unbalanced nutrition needs, and women suffering more from comorbid diseases, such as osteoporosis,fractures of bone hip, and other degenerative diseases. This study aimed to investigate the relationship between frailty incidence and polypharmacy in the elderly group in Melinggih Village, Gianyar, Bali. This cross-sectional study used secondary data from interviews and questionnaires conducted in December 2022. Samples were collected using a total sampling method. The analysis was conducted using univariate and bivariate analysis, with Chi square tests applied using SPSS 25.0 for Windows. Ninety-five of the 97 patients involving thisstudy had a history of treatment with < 2 types of drugs (non-polypharmacy), while 2 patients with more >2 types of drugs (polypharmacy). No significantly relationship between the number of drugs consumed and frailty status (p= 0.303). In conclusion, no relationship between frailty and polypharmacy is reported in Melinggih Village, Gianyar, Bali.